The arrangement inside the arrangement: three cases of Egberto Gismonti’s pieces for a Brazilian Ensemble (Orfeu, 2023)
This work belongs to the field of the creative processes in music envolved in the elaboration of 3 arrangements ("Maracatú", "Palhaço" and "Água e Vinho") carried out by the author of this article based on themes composed by Egberto Gismonti and the discussion of its surroundings. Methodology: from the analyses of the original works (audio and scores) and the description of the elaborated arrangements, it is observed that all arrangements carry out some kind of musical collage in their parts, in a process similar to the ones used in some works by Heitor Villa-Lobos, as described by the retired composition teacher of USP (University of São Paulo) Willy Corrêa de Oliveira (1938). Complementing methodological procedures, some analyses were made based on extra-musical elements and aspects of musicalities found in Brazilian manifestations according to the genre of composition: “Maracatu”, “Guarânia”, Brazilian Song and “Choro”. Thus, as a result, from a discussion on the rapsodic procedure in the arrangement of popular music, it points to the possibility of a metalinguistic conception of the arrangement as collage, or the arrangement within the arrangement. Concluding, it is finished by conceptualizing collage procedure within the possible perspective of postmodernism in music
Keywords: musical arrangement; Egberto Gismonti; brazilian jazz; brazilian typical orchestra; musical collage